Bridging the gap from hydrological to biogeochemical processes using tracer-aided hydrological models in a tropical montane ecosystem - Pesántez, Juan Pablo (2023)
How simple or complex catchment models need to be is still unclear particularly for tracer-aided models that go beyond hydrograph fitting. Here, we take advantage of a sub-daily hydrometric and tracer data set from a tropical montane (páramo) experimental catchment to fill this knowledge gap. We evaluated six conceptual rainfall-runoff |°model structures with different complexity that represent the perceptual understanding of the catchment's hydrological functioning. The models solved conservative and reactive tracer mass balances to simulate streamflow, stable isotopes, and DOC concentrations and were assessed for performance and parsimony using three calibration targets (discharge only, discharge and stable isotopes, and discharge and DOC), resulting in 18 model configurations. Although all models satisfied the discharge calibration (KGE > 0.8), differences arose when considering tracer transport. The more complex models outperformed the simpler ones in terms of goodness-of-fit and parsimony, indicating that the catchment streamflow response consisted of quick near-surface flow and tracer contributions, more mixed flow through the two main soil types (Andosols and Histosols), as well as flow from the well-mixed shallow fractured rock (up to 20 m depth). The bedrock flow pathway contributed up to ∼25% of total flow during baseflow conditions. This study provides a benchmark experiment to identify hydrological and biogeochemical behavior in tropical montane catchments using relatively parsimonious tracer-aided hydrological models.